Generation-3 Polyamidoamine Dendrimer-Silica Composite: Preparation and Cd(II) Removal Capacity - Augustus N. Ebelegi; Nimibofa Ayawei; Azibaola K. Inengite; Donbebe Wankasi (Journal of Chemistry)
Generation-3 polyamidoamine (PAMAM) dendrimer was implanted on silica to produce a very good adsorbent (G-3 PAMAM-SGA). The composite was characterized and used for the removal of Cd(II) ions from aqueous solution. Kinetic data fit the Lagergren pseudo-second-order model and also follow the intraparticle diffusion kinetic model to an extent, which is an indication that the sorption process is controlled by both mechanisms: intraparticle/film layer and adsorption inside the pores/crevices of the composite. Equilibrium sorption data of Cd(II) on G-3 PAMAM-SGA fit the Freundlich isotherm (R2 = 0.9993) which is indicative of multilayered adsorption that occurred on heterogeneous surfaces. The ΔG° values for all temperatures studied were negative, which indicated a spontaneous and feasible process. The result implies that G-3 PAMAM-SGA is a promising adsorbent for microscale scavenging of Cd(II) ions in aqueous solutions.